The Effects of a Diet Containing Yoghurt with Krill Oil Consumed by Rats During Their Pregnancy on Long Bones of Their Offspring - Halil Yalçın; Ayşe Nur Özen Duran; Yasin Demiraslan; Zeki Erol; İftar Gürbüz (Veterinary Sciences and Practices)
The use of calcium, vitamins, minerals, and omega 3 fatty acids during pregnancy are recommended to support the bone development of infants. The aim of this study is to feed pregnant rats with the probiotic yoghurt mixed with krill oil, which is rich in these features, and examine the morphometric development of long bones in their offspring. For this purpose, a total of twelve 2-month-old offspring including 6 in the experimental group (offspring of pregnant rats fed with yoghurt mixed with krill oil) and 6 in the control group (offspring of pregnant rats fed a standard feed), were used in the study. When they became 2 months old, their biometric measurements were taken. After euthanasia, long bones of the offspring (Humerus, antebrachium, femur, ossa cruris) were cleaned by maceration. These bones were photographed. Morphometric measurements of the length and width of these bones were made using the Image J program. In the SPSS (20.0 Version) program, the parameters were compared between the right and left leg bones and between the control and experimental groups by running the Independent Samples T test. Additionally, Pearson’s correlation test was applied between the parameters. The results of the study indicated that this diet with krill oil and yogurt consumed by pregnant rats had positive effects on the length parameters of the bones and biometric parameters of their offspring.